2017
DOI: 10.1155/2017/4807064
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Optimization of Paper-Based SERS Substrate for Potential Label-Free Raman Analysis of Seminal Plasma

Abstract: Characterization and optimization of paper SERS substrate were performed in detail, in which morphologies and distribution of silver nanoparticles (AgNPs) on the paper substrate pretreated with different concentrations of NaCl and the subsequent soaking with colloidal AgNPs for different period of time were evaluated. Our results show that both NaCl concentration and soaking time with AgNPs have a significant influence on SERS enhancement, showing that an optimal EF of 2.27 × 10 7 was achieved when the paper s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 39 publications
(43 reference statements)
2
7
0
Order By: Relevance
“…1 ]. Several recent studies have demonstrated the utility of different approaches for improving the loading (e.g., prior soaking of paper in NaCl, Glycidyl-trimethyl-ammonium chloride (GTAC)] 85,86 . The advantage of dip coating/immersion method is its ability to deposit NPs with different shapes, sizes, and compositions on the paper 87−89 .…”
Section: Paper-based Sers Substratesmentioning
confidence: 99%
“…1 ]. Several recent studies have demonstrated the utility of different approaches for improving the loading (e.g., prior soaking of paper in NaCl, Glycidyl-trimethyl-ammonium chloride (GTAC)] 85,86 . The advantage of dip coating/immersion method is its ability to deposit NPs with different shapes, sizes, and compositions on the paper 87−89 .…”
Section: Paper-based Sers Substratesmentioning
confidence: 99%
“…The time of soaking was ∼30 min uniformly for all of the substrates studied. However, this time also affects the loading of NPs and has been studied extensively by Huang et al, 58 wherein they observed that soaking for 1 h procured excellent SERS results. The absorption of NPs on a substrate will enhance the EM field in sensing because of its ability achieved through the excitation of LSPR.…”
Section: Experimental Detailsmentioning
confidence: 99%
“…Example of how characteristic ET bands (highlighted with grey areas) are observed in LF‐SERS spectra of a variety of human biofluids of healthy donors. SERS spectrum of (a) ET [19] is compared to SERS spectra of (b) erythrocytes lysate [19], (c) serum [29], (d) gingival crevicular fluid [28], (e) seminal plasma [50] and (f) cerebrospinal fluid [32]. All spectra were obtained with an excitation at 785 nm, and using Ag nanoparticles as substrates, with the exception of (f), for which Au nanoparticles were used.…”
Section: Et In Lf‐sers Of Biofluidsmentioning
confidence: 99%
“…Spectral data of (e) and (f) were obtained from fig. 2d in [50] and fig. 4A in [32], respectively, by using the open software web plot digitalizer [57].…”
Section: Et In Lf‐sers Of Biofluidsmentioning
confidence: 99%